Latawce - Dzianowicz, Beata (Poland : Eureka Media, 2008)
In 2006, a film course called "Kabul - My City" was held at the Art School in Kabul. Students were given cameras, and professional help from a young Polish director by the name of Jacek Szaranski. The students came up with the ideas for their films and the style in which they would show Kabul. They focused their lenses on their closest surroundings - neighbors' children, the ubiquitous kites and themselves. "Kites" has become a record of present day Kabul from the perspective of an Afghan teenager. It also became a story about how a passion for film is awakened, about the difficulty of asking questions, and about the courage needed to hear the answers.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films